Existence of a solution of an infinite system of weighted Atangana-Baleanu fractional integral equation via measure of non-compactness on a tempered sequence space. - Yeasmin, Fahmida Nishat; Ahmed, Tazuddin (Communications in Mathematics and Applications, 2026)
The goal of this study is to investigate the existence of a solution of an infinite system of weighted Atangana-Baleanu fractional integral equation via a newly constructed generalised form of the Darbo’s fixed-point theorem on a tempered sequence space. Furthermore, an example has been illustrated to portray the effectiveness of the obtained result.